SELLER PERSPECTIVE ON AGROBAZAAR ONLINE PLATFORM: SALES AND PURCHASE FEATURES - Kamaruddin Radzuan; Mazri Yaakob; Faisal Zulhumadi; Mohd Kamarul Irwan Abdul Rahim (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
This research examines how the sales and purchase features of the Agrobazaar Online platform influence seller satisfaction and business performance. Despite its potential, sellers face challenges in maximizing the platform’s features, such as limited customization options and insufficient promotional tools compared to more established platforms like Shopee and Lazada. Using a qualitative case study approach, in-depth interviews were conducted with five sellers registered under the Federal Agricultural Marketing Authority (FAMA), focusing on their experiences with Agrobazaar Online’s store design, shopping cart, payment processing, and promotional features. Data were transcribed, coded, and analyzed thematically using NVIVO software. The results indicate that while the platform’s features positively affect seller satisfaction, gaps remain in its promotional capabilities, product catalogue management, and buyer-seller communication. Sellers recommended incorporating features from other popular e-commerce platforms, expanding marketing via social media, and enabling business matching to enhance networking opportunities. These findings suggest that improving the platform’s functionality and marketing tools can significantly impact seller satisfaction, leading to better business outcomes. The study provides valuable insights for developers of Agrobazaar Online to enhance the platform’s competitiveness and help Malaysian sellers maximize their business potential.